Topologically Safe Curved Schematisation. (1st August 2013) - Goethem, Arthur van; Meulemans, Wouter; Reimer, Andreas; Haverkort, Herman; Speckmann, Bettina
<x xml:space="preserve">Abstract</x> Traditionally schematised maps make extensive use of curves. However, automated methods for schematisation are mostly restricted to straight lines. We present a generic framework for topology-preserving curved schematisation that allows a choice of quality measures and curve types. The framework fits a curve to every part of the input. It uses Voronoi diagrams to ensure that curves fitted to disjoint parts do not intersect. The framework then employs a dynamic program to find an optimal schematisation using the fitted curves. Our fully-automated approach does not need critical points or salient features. We illustrate our framework with Bézier curves and circular arcs.